Novel slow-sound lattice absorbers based on the sonic black hole - Chua, Jun Wei; Li, Xinwei; Yu, Xiang; Zhai, Wei (Composite structures, 2023)
[Display omitted] •The work presents a slow-sound lattice sound absorber with sonic black hole plates.•Samples were printed successfully using the vat photopolymerization technique.•Sound absorption performances of the proposed lattices outweigh the truss lattices.•The proposed lattices exhibit both resonance and sound speed reduction mechanisms. The advent of additive manufacturing enabled rapid progress in the research of lattice structures, such as truss lattices, for sound absorption applications. Thus far, the sound absorption coefficient curves of truss lattices are typically characterized by alternating regions of high and low coefficients, reminiscent to that of Helmholtz resonators. The relatively poor sound absorption performances of such lattices prompt a need for an alternative sound absorption mechanism to improve their performances. In this work, we propose to incorporate a series of thin parallel plates with circular holes resembling the profile of a sonic black hole (SBH) into truss lattices for the design of a novel class of slow-sound lattice absorbers (SSLA). Four truss lattices, based on the mimicry of Bravais lattices, are considered. Samples were manufactured using stereolithography and the sound absorption properties were measured using an impedance tube. A significant increase in the sound absorption coefficients throughout a broadband frequency range from 1000 to 6300 Hz was observed with the addition of SBH plates. Finite element modelling reveals that the SSLA exhibits both the frequency-dependent resonant cell mechanisms of the lattice absorber and the time-dependent sound speed retardation effects of the SBH. Compression tests also reveal significant improvements to the specific energy absorption and absorption efficiency for some of the structures. Overall, this work demonstrates the potential and a conceptual advance with the adoption of additional plates to induce the sound speed reduction mechanism in the design of sound-absorbing lattices.